The Impact of Social Media on Language Evolution and Generation Z Identity: A Synthesis - Nurul Jumiati (LPPM Institut Pendidikan Nusantara Global, 2026)
This research provides a comprehensive synthesis of the impact of social media on language evolution and the formation of Generation Z identity. In an increasingly advanced digital era, social media has become a primary communication tool triggering significant linguistic changes. This study aims to analyze language simplification, syntactic shifts, and the role of slang in shaping social identity. The method employed is a systematic literature review combining findings from three major studies on digital sociolinguistics. Findings indicate that social media encourages linguistic economy through abbreviations and phonetic spellings. Furthermore, digital platforms facilitate the emergence of